A dynamic pricing approach to electricity prices in the Indian context. (4th March 2014) - Desai, Kinnary R.; Dutta, Goutam
In this paper, we study the mechanism of dynamic pricing of electricity and its opportunities in the Indian context. We compare the economic efficiency of dynamic pricing vis-à-vis the traditional flat tariff of electricity. We analyse various ways in which dynamic tariff can be introduced in the electricity market and we show the Indian experience in this regard. We consider the state of Maharashtra, in particular, to understand how the time of day (TOD) pricing system has been introduced and how it is more efficient than the flat tariff approach. We develop a mathematical model using pseudo-real data (as per the advice of a renowned sector expert) to show how TOD tariff is more efficient than flat tariff and how real-time pricing (RTP) tariff is associated with the uncertainty of electricity bills. We further emphasise how the dynamic pricing system can be modified to increase its efficiency.